Advanced Acceptor‐Substituted S, N‐Heteropentacenes for Application in Organic Solar Cells. Issue 42 (29th May 2021) - Kraus, Teresa; Lucas, Sebastian; Wolff, Pascal; Aubele, Anna; Mena‐Osteritz, Elena; Bäuerle, Peter
Abstract: Ambifunctional heterpentacenes with the heteroatom sequence SSNSS in the ladder‐type backbone were used either as donor or as nonfullerenic acceptor in solution‐processed bulk‐heterojunction solar cells. Different acceptor moieties and side chains were inserted. Synthesis and characterization of the systematically varied structural motifs provided insight in structure‐property relationships. Moreover, a dimeric heteroacene was synthesized, and the optoelectronic properties were compared to those of its monomeric counterpart. Abstract : Functionalized S, N ‐heteropentacenes SN5' comprising annulated thiophene and pyrrole rings with the heteroatom sequence SSNSS in the ladder‐type backbone were developed with systematically varied structural motifs. Tunable frontier orbital energies allowed their application either as donor or as nonfullerenic acceptor in solution‐processed bulk‐heterojunction solar cells.